Merlin immunohistochemistry is useful in diagnosis of tumours within the spectrum of biphasic hyalinizing psammomatous renal cell carcinoma. Issue 5 (16th August 2022) - Collins, Katrina; Hwang, Michael; Antic, Tatjana; Paintal, Ajit; Argani, Pedram; Matoso, Andres; Gopinath, Arun; Baskovich, Brett; Mehra, Rohit; Williamson, Sean R.; Idrees, Muhammad T.; Barletta, Justine A.; et al.
Abstract : Aims: Biphasic hyalinizing psammomatous (BHP) renal cell carcinoma (RCC) is a newly described emerging entity within the spectrum of papillary RCC in the WHO 2022 classification. Molecular analyses have discovered that BHP RCC consistently harbour somatic mutations in the neurofibromin 2 (NF2) gene. The NF2 gene product, merlin, is known to primarily function as a tumour suppressor. Merlin protein loss correlates closely with the presence of NF2 mutations in benign and malignant tumours arising in different sites. In the present study we explored the role of merlin immunohistochemistry (IHC) in tumours within the spectrum of BHP RCC to determine the diagnostic utility of this marker. Materials and Methods: We performed merlin IHC in 13 BHP RCC, 18 papillary RCC, 10 TFE3 ‐translocation RCC, 15 TFEB‐ altered RCC (including 13 TFEB ‐rearranged and 2 TFEB ‐amplified), and 10 mucinous tubular and spindle cell carcinomas of unknown mutational status. Results: Unequivocal loss of merlin expression in >90% of the tumour cells was observed in 12/13 BHP‐RCC (92%), with the remaining tumour demonstrating weak focal cytoplasmic expression in 10% of the tumour. In contrast, merlin was diffusely or multifocally expressed in all papillary RCC, TFE3 ‐translocation RCC, and TFEB ‐altered RCC, as well as in 70% of mucinous tubular and spindle carcinomas. Conclusions: In this study, merlin IHC was 92% sensitive and 94% specific for BHP RCC. These data suggest that merlin IHC is a reliable surrogate marker for the presence of underlying NF2 gene inactivation, being diagnostically useful to identify BHP RCC. Conclusions: In this study, merlin IHC was 92% sensitive and 94% specific for BHP RCC. These data suggest that merlin IHC is a reliable surrogate marker for the presence of underlying NF2 gene inactivation, being diagnostically useful to identify BHP RCC. Abstract : Merlin (NF2) immunohistochemistry is a useful diagnostic tool to distinguish between tumors within the spectrum of biphasic hyalinizing psammomatous renal cell carcinoma (BHP RCC) and morphologic mimics.